Forschungen in Ala Nova/Schwechat Die Auswertung der Grabungen 2009/2010 im pannonischen Donaukastell und in dem Gräberfeld Schwechat Frauenfeld - Maspoli, Ana Zora (Verlag der Österreichischen Akademie der Wissenschaften, 2023)
Until now, forts and cemeteries at the Pannonian Limes have rarely been the focus of research, and thus both the interior construction of the Pannonian fort of Ala Nova and an associated cemetery outside of it have only been known through isolated and random discoveries. The analysis of two archaeological investigations (Bundesdenkmalamt/Archäologie Service 2009/2010) in the fort Ala Nova as well as in the associated cemetery make it possible for the first time to work out the Metadaten 3 chronological classification of the construction and (post-)use phases of the fort and the fort area (1st half of 3rd to late 4th or early 5th century AD) and the cemetery (3rd century AD) as well as the burial rites of the biritual cemetery. For the analysis, the features with their relative chronological sequence and the artefacts from the area of two military barracks and a section of the rampart ditch of the fort, as well as from 136 burials, some pits and a ditch in the cemetery were taken into account.